2023
DOI: 10.3897/neobiota.82.87264
|View full text |Cite
|
Sign up to set email alerts
|

Chelonian challenge: three alien species from North America are moving their reproductive boundaries in Central Europe

Abstract: Biological invasions by alien species have substantial economic impacts and are a major driver of the ongoing decline and loss of biodiversity. Through humans, the North American pond slider (Trachemys scripta) has acquired a global distribution over the last decades and is currently listed among the worst invasive reptile species. However, in more recent times, other freshwater chelonian species have increasingly been recorded far outside their native distribution ranges as well, not only on the same continen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Previous studies found that aquaria and garden ponds may act as sources of invasive species (Chucholl, 2013; Patoka et al, 2014; Soes et al, 2011; Van Den Neucker et al, 2017), e.g. the red-eared slider ( Trachemys scripta elegans ) (Tietz et al, 2023), water hyacinth ( Pontederia crassipes ) (Olden et al, 2021), signal crayfish ( Pacifastacus leniusculus ) (Chucholl et al, 2021). In this sense, without the indispensable knowledge and education about invasive species, garden pond owners and garden centers can pose a threat to native biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that aquaria and garden ponds may act as sources of invasive species (Chucholl, 2013; Patoka et al, 2014; Soes et al, 2011; Van Den Neucker et al, 2017), e.g. the red-eared slider ( Trachemys scripta elegans ) (Tietz et al, 2023), water hyacinth ( Pontederia crassipes ) (Olden et al, 2021), signal crayfish ( Pacifastacus leniusculus ) (Chucholl et al, 2021). In this sense, without the indispensable knowledge and education about invasive species, garden pond owners and garden centers can pose a threat to native biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…The pond slider Trachemys scripta is regarded in the European Union as an invasive species (IAS) due to its reproductive success and establishment of viable populations not only in the Mediterranean region [STANDFUSS et al 2016] but also in more northern European countries like Germany [TIETZ et al 2022]. It is known, that in some parts of the invaded region, it negatively impacts the native European pond turtle [STANDFUSS et al 2016;JABLONSKI et al 2017], however, the impact on local communities and the ecosystem is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These authors elucidated for the first time the invasive potential of the Trachemys populations in Slovenia and provided crucial knowledge for the conservation and management of the native European pond turtle. Recently, another study by TIETZ et al [2022] genetically confirmed the successful reproduction of the alien pond slider also in Germany.…”
Section: Introductionmentioning
confidence: 90%
“…However, lacking a proper assessment of the species on the island, its actual local distribution is partially unknown. Standfuss et al [64] and Tietz et al [81] genetically proved the invasive potential and the successful reproduction of T. scripta in Slovenia and Germany, respectively. Evidence of successful reproduction of the pond slider in the Italian peninsula was reviewed by Ficetola et al [76]; see also [82].…”
Section: Remarksmentioning
confidence: 99%